Development of an Animated Video on Atomic Structure Material Integrated with Qur’an for Online Learning Using PowToon Web Apps - Santoso, Raliandana Louise; Kamaludin, Agus; Safarova, Aytan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Qur’an science learning is needed so that students are intelligent academically, attitudinal, and spiritually. This study aims to develop an animated video of the integrated atomic structure material of the Qur'an using the PowToon web app. The method used in this study is the 4D Re search & Development (R&D) model (Define, Design, Development, and Disseminate). The products developed were assessed by media experts, material experts, reviewers, and student responses. The results of product quality assessment by material experts get a percentage of 95% in the excellent category, media experts get 90% in the outstanding variety, and reviewers get a rate of 94% in the excellent category. Class X high school students responded positively to the products developed with a percentage of 94%. Based on the assessment results, the video can be used as an online learning medium for Qur’an-integrated atomic structure material to increase gratitude to Allah SWT. Keywords: the animated video, integrated qur’an, atomic structure, powtoon